Korelasi Antara Penguasaan Kosakata Siswa Dengan dan Pencapaiannya Dalam Pemahaman Membaca - Gina Larassaty (Universitas Pancasakti Tegal, 2019)
This research deals with the correlation between students vocabulary mastery and their achievement in their reading comprehension. The data were taken from 33 students from class X-TKJ of SMK As Sakienah in Sliyeg The writer used quantitative method by Pearson Product Moment. From the calculation by using product moment formula, it was found out that the coefficient correlation from this research is 0,8409.. It can be concluded that there is positive and high correlation level between students’ vocabulary mastery and their achievement in reading comprehension. This research used significance level 5%. From the hypothesis testing result, it was found that r_count is 0,8409 >r _table 0,3494. Based on the fact, it can be concluded that Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. So, there is significance correlation between students’ vocabulary mastery and their achievement in reading comprehension.